Accionar de enfermería en la prevención de la drogadicción en adolescentes. - Guamán Caguana, Manuel Ramón (2022)
Drug addiction is currently a public health problem worldwide, affecting all age groups, however, according to recent statistics, adolescents are the most likely to fall into the world of drug addiction, so Therefore, this bibliographic review aims to identify nursing actions in the prevention of drug addiction in adolescents, in addition to the causal factors that lead to this problem, thus allowing nursing interventions to be proposed with a preventive approach. In this bibliographic review, a descriptive methodology was used, through the search for scientific information indexed in databases such as: Scielo, Dialnet, Scopus, Pubmed, Elsevier, Virtual Health Library, ProQuest, Google Scholar, Mayo Clinic, published from 2015 to 2022, with the descriptors: nursing, drug addiction, adolescent and prevention. After the documentary review, it was determined that the nursing actions have a preventive approach and are directed to three large groups, family, personal and community partner where several examples are cited, such as: education by parents, affective communication, family union , application of playful games, leisure activities, physical activity, reflexology, social integration, personal motivation strategies, active listening, integrating social actors, adaptation of the environment, among others, reaching the conclusion that all preventive actions must be executed in combination, since they have shown greater effectiveness when applied.